Կիրովական քաղաքի հասարակական սննդի ցանցում եղած խնդիրները 1960-ական թվականների երկրորդ կեսին - Սուքիասյան, Համո (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
In order to fight against the abuses in the public food network of the Armenian SSR, state, party and public control bodies were engaged. Problems existed both in the capital Yerevan and in the regions. In the spring of 1967, in order to identify the problems in the Kirovakan city’s public catering network, the commission conducted inspections and found out that in the canteens and buffets of the city’s industrial enterprises there were widespread shortages of high-demand products, cases of non-observance of trade rules, under-measurement, under-weighing and under-accounting. The extensive reference prepared on the results of the inspection is an important source for the study of the economic history of Kirovakan.
Keywords: Պատմություն; Սննդարդյունաբերություն